Comparison of Dimensional Stability of Alginate Impressions by Spraying 0.5% Sodium Hypochlorite Against Kepok Banana Peel Extract (Musa paradisiaca Linn.) - Cindy Denhara Wijaya; Mangatas Halomoan Parluhutan Hutagalung; Laurencia Kasih Putri Hulu (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: The process of impressions of hard and soft tissues in the oral cavity is a fairly routine activity in dentistry. Alginate is an irreversible elastic impression material that is often used. Alginate can be disinfected using soaking or spraying techniques. This disinfection solution itself has side effects that are quite serious for patient health. This study aimed to find out Comparison of the dimensional stability of alginate impressions by spraying 0.5% sodium hypochlorite against kepok banana peel extract (Musa paradisiaca Linn.). Methods: This study was experimental research. The research object used was dimension of alginate impressions which were grouped into control and treatment groups. Assessment of the projection value of the antero-posterior (AP) and cross arch (CA) lines was carried out with digital calipers. Data analysis was carried out with the help of SPSS version 25 in univariate and bivariate. Results: The results of this study showed that the mean value of the AP and CA lines in the kepok banana peel extract treatment group did not show a significant difference with the control treatment (sodium hypochlorite 0.5%), p-value> 0.05. Conclusion: Spraying kepok banana peel extract with various concentrations did not cause changes in the dimensions of the alginate impressions.